Implementasi Nilai-Nilai Zuhud dalam Kehidupan Sosial Kiai Pondok Pesantren Al-Amien Prenduan - Badriyah, Anisatul; Amalih, Ihwan (Aqlania, 2023)
This article will examine the implementation of zuhud values in social life by focusing on the zuhud values implemented by the Kyai of al-Amien Prenduan Islamic Boarding School. In social life, it is very difficult to increase the spiritual soul in people because there are so many offers of change that have negative effects. One of the negative effects is the creation of a materialistic attitude and a hedonistic lifestyle. However, this can be overcome by the ascetic values applied by the Kiai of Al-Amien Prenduan Islamic Boarding School. The research method used is a field qualitative research method. The researcher chose the focus of research that will be discussed later is how the meaning of zuhud by kiai of the Al-Amien Prenduan Islamic Boarding School and how to implement zuhud values in social life nynyamong kiai of the Al-Amien Prenduan Islamic Boarding School. The results of this study are first, zuhud according to the kiai of Al-Amien Prenduan Islamic Boarding School is to free the heart from worldly things and zuhud also means to use the favors or gifts of Allah as needed not as desired. And secondly, the implementation of the values of zuhud kiai pondok pesantren al-Amien Prenduan not only for his own person but for his family, students and the surrounding society. The zuhud values applied are simplicity, sincerity, ukhuwah Islamiyah, patience, honesty, and doing something worldly as a mediator for the hereafter.